2018
DOI: 10.5897/jphe2017.0980
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels among Fayoum governorate population (Egypt): Community-based survey

Abstract: Physical inactivity is one of the most important public health problems in the 21st century. It plays an active role in the prevention of both non-communicable diseases and premature death. A communitybased survey was conducted to assess the level of physical activity among household population and to identify associated demographic factors of physical inactivity. A sample of 5000 households was selected by a multi-stage stratified cluster random sample. A standardized world health organization (WHO) structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…Also, this study showed a statistical significant relation between levels of physical activity with the education status of the female osteoporotic patients. The result of the current study was almost the same as the Egyptian study done by Naglaa & Asmaa, (2018) who reported a positive association between physical activity and the educational level of study participants. A study done in Cairo, Egypt reported level of formal education of a studied woman was significantly associated with physical inactivity (Mowafy et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, this study showed a statistical significant relation between levels of physical activity with the education status of the female osteoporotic patients. The result of the current study was almost the same as the Egyptian study done by Naglaa & Asmaa, (2018) who reported a positive association between physical activity and the educational level of study participants. A study done in Cairo, Egypt reported level of formal education of a studied woman was significantly associated with physical inactivity (Mowafy et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Concerning the association between physical activities and social demographic data, the results of the present study revealed that there was a statistical significant relation between levels of physical activity of the female osteoporotic patients as regards their place of residence. The same scenario was observed by Naglaa & Asmaa, (2018) who reported there was a significant association between socio-demographic characteristics of the respondents with both the vigorous and moderate-intensity recreational activities. According to Mowafy et al, (2019), they reported urban residents was consistently associated with physical inactivity across women and combined group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…[5,6] The situation could worsen owing to a lack of employee organizational commitment which is a significant driving force of employee turnover intention in several sectors. [7,8] Although nurses are crucial partners in the healthcare sector and among the frontline healthcare practitioners required to achieve effective healthcare-related programs, numerous challenges confronting hospitals today are frequently attributed to a lack of nurses' commitment and performance, given that nurse commitment is a critical issue in achieving overall hospital performance and pursuing the delivery of an effective healthcare system. [9][10][11][12] Commitment is strongly related to performance because committed nurses engage in more extra-role activities and behaviors such as creativity and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ] The situation could worsen owing to a lack of employee organizational commitment which is a significant driving force of employee turnover intention in several sectors. [ 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%